BUDIDAYA ORGANIK KEDELAI PADA SISTEM AGROFORESTRI MENGGUNAKAN PUPUK HAYATI - Steviana Baity; Djoko Purnomo; Trijono Djoko Sulistyo (Universitas Sebelas Maret, 2015)
Organic cultivation in egroforestry system by biofertilizer potentialy conducted for soybean. Soybean cultivation in agroforestry system there are several limitations but it have to effort since the area of ideal land decreasing year by year. The aim of the research by experiment method is increasing yield of soybean by organic cultivation in agrofrestry system either quality or quantity. The experiment design is randomized block design (RBD) with two factor trearments. The first factor are kinds of variety (Grobogan and Local) as mainplot and the second one are biofertilizer duration (no biofertilizer as control, 4, 5, 6, 7 weeks applies ones a week). So there are 10 combination treatments and replicated three times for each of them.